POSISI DAN REPOSISI KEPERCAYAAN LOKAL DI INDONESIA - SIRAIT, ARBI MULYA; NAFISA, FITA; OKTIA D, RIFDAH ASTRI; JATMIKO, RUMPOKO SETYO (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2015)
Indonesia as a pluralistic nation judged on the diversity of religion, belief, tradition, art and culture that has long thrive and ï¬‚ourish in the midst of life. Comes from the fact that a plurality, debate arose between communities who admitted he was most true among others. The polemic between the religions recognized in Indonesia with local beliefs that are spread throughout the region is one of the problems in the relationship between religion and the state. Problems that occur in the study of religion and society at the local faiths is the status, human rights and rights as citizens. Completion of this problem is the need for dialogue between the state, the dominant religious and local beliefs. Examples of local beliefs that have done such a solution is the Islamic belief in Lombok MadraisWetutelu in Cigugur. Both the trust is deemed to have been successful in the aspects of religious tolerance and its relationship with the state. Mutual relations between the state as protector of its citizens and citizens comply with its obligations is the purpose of the concept of interreligious tolerance. As part of the plurality of Indonesia, local belief should be positioned as a cultural heritage that must be considered his rights by the state.